c+(3c)+(2.5c)=60

Simple and best practice solution for c+(3c)+(2.5c)=60 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for c+(3c)+(2.5c)=60 equation:


Simplifying
c + (3c) + (2.5c) = 60

Combine like terms: c + (3c) = 4c
4c + (2.5c) = 60

Combine like terms: 4c + (2.5c) = 6.5c
6.5c = 60

Solving
6.5c = 60

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Divide each side by '6.5'.
c = 9.230769231

Simplifying
c = 9.230769231

See similar equations:

| (7-x)(x^2+20)= | | (x-3)=50 | | 8+2.50x=30 | | 6x+6=-8+2x+22 | | 0.23(10000)-0.04y=0.06(y+10000) | | 12-4m=36-12m | | x^3-200x^2+2x=0 | | 8k+5=2k-15 | | 3-2x^2=7 | | -4(-x-3)= | | 7+57=q | | 2(5x+3)+11x= | | 7+57= | | 8+10x=-11x | | (7x+4)=(18x-6) | | 2(l+0.2l)=240 | | 2(18)=p | | dx=(x^2-1)*dy | | 16x=25y | | 0.16(y-9)+0.02y=0.06y-0.9 | | 16x+25y=0 | | 7w-2w= | | -3(6p+5)-2(5-17p)=3(9+5p) | | x^2-17=81 | | 5/6-x/18=1/9 | | 7b=3-2b | | 4.71=3.14a(2) | | (-5x)+3x= | | 43+34= | | 2w=40 | | 2x^2+8x+8=8 | | 3x-15=8x+7 |

Equations solver categories